2015
DOI: 10.17269/cjph.106.4762
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and smoking in North Americans of Chinese ancestry: A systematic review

Abstract: were extracted from Canadian and American studies for population characteristics, study design, measures of smoking and acculturation, and findings regarding smoking rates and associations between smoking and acculturation. SYNTHESIS:The literature search identified 147 articles, and 14 met inclusion criteria. Three studies were based on Canadian samples and the remaining 11 were from the United States. Of the 14 papers, 3 reported findings for youth and 11 for adults. Among adults, daily smoking rates were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
(87 reference statements)
2
14
1
Order By: Relevance
“…Associations in this study were consistent with social influences associated with Western norms on behaviors including alcohol intake, smoking, and diet and thus showed parallels to the literature on acculturation and smoking [39][40][41], diet [41][42][43], and physical activity [42,44]. Women who have been in the US longer often have a higher Western diet intake, particularly higher intakes of meat, sweets, and sweetened beverages, a greater likelihood of smoking, and higher levels of physical activity [45][46][47]. In prior work, social network composition has differed by nativity with immigrant (vs. US-born) women having larger proportions of family in their networks [48,49].…”
Section: Plos Onesupporting
confidence: 82%
“…Associations in this study were consistent with social influences associated with Western norms on behaviors including alcohol intake, smoking, and diet and thus showed parallels to the literature on acculturation and smoking [39][40][41], diet [41][42][43], and physical activity [42,44]. Women who have been in the US longer often have a higher Western diet intake, particularly higher intakes of meat, sweets, and sweetened beverages, a greater likelihood of smoking, and higher levels of physical activity [45][46][47]. In prior work, social network composition has differed by nativity with immigrant (vs. US-born) women having larger proportions of family in their networks [48,49].…”
Section: Plos Onesupporting
confidence: 82%
“…With time spent in the host country, immigrants’ health deteriorates to become similar to that of the local population (Gushulak et al, 2011). Researchers have hypothesized that the deterioration reflects an acculturation process whereby immigrants take cultural characteristics and behavioral habits of the non-immigrant host population (Gotay, Reid, Dawson, & Wang, 2015). The relationship between the acculturation and health is not clear either.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the acculturation and health is not clear either. The lifestyle changes within the acculturation process can differ between men and women (Gotay et al, 2015). Immigrants may take lifestyle habits that either hinder their health, such as being more sedentary, or eating more processed food, or lifestyle habits that benefit their health, such as reducing their tobacco consumption (Gotay et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has identified several risk factors associated with elevated smoking rates among Chinese American men, including level of acculturation, symptoms of anxiety and depression, low perceived risk associated with smoking, and social environmental influences, such as peer smoking and smoking norms . Although the negative consequences of smoking on health outcomes have been well documented among smokers in the general populations, there is a paucity of information on a comprehensive examination of the relationship between cigarette smoking and health conditions among older Chinese Americans.…”
mentioning
confidence: 99%